Hormonal assay in lactating male goat - KUMAR, DAVENDRA; SAHA, S; CHATURVEDI, O H; KUMAR, S; MANN, J S; MITTAL, J P; SINGH, V K (The Indian Journal of Animal Reproduction, 2023)
This communication reports a case of an extremely rare incidence of lactation in an adult fertile male goat. The serum concentration ofprolactin, progesterone, testosterone and estradiol hormones of a lactating male, normal male and female goat were found to be 5.40, 2.40 and 1.90 ng/ml, 144.00, 22.60 and 1.90 nmol/1, 5.00, 18.60 and 0.748 nmol/1 and 62.84, 90.97 and 94.80 pmol/1, respectively. The high concentration ofprolactin and progesterone with low concentration of testosterone and estradiol hormones in the lactating male goat as compared to normal male might have been responsible for lactation in the male goat.